PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA (Persero) KANTOR CABANG CIPUTAT TANGERANG SELATAN - Angga Putra Aditama; Hamdi Supriadi (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of discipline and work motivation on employee performance at PT. Pos Indonesia Ciputat South Tangerang Branch Office. The method used in this research uses quantitative methods. The sampling technique used the Slovin formula and a sample of 57 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that discipline has a significant effect on employee performance with a coefficient of determination value of 70.3% and the hypothesis test obtained t count > t table or (7.332 > 1.673). Work motivation has a significant effect on employee performance with a coefficient of determination value of 74.9% and hypothesis testing obtained a value of tcount > ttable or (8.394 > 1.673). Discipline and work motivation simultaneously have a significant effect on employee performance with the regression equation Y = 7.308 + 0.355X1 + 0.465X2. The coefficient of determination or contribution of simultaneous influence is 80.3%, while the remaining 19.7% is influenced by other factors. Hypothesis testing obtained a value of F count > F table or (49.183 > 2.78). The correlation coefficient value of discipline, work motivation and employee performance was simultaneously obtained at 0,494, while the remainder was (100-49,4) = 50,6% influenced by other factors. Simultaneous correlation coefficient test obtained a correlation coefficient value of 0,803, which is in the interval 0,600-0,799.